KONFLIK TANAH DI ARSO PAPUA 1980-2002 (History Department, Semarang State University and Historian Society of Indonesia, 2012)
A land problem in Indonesia, including Papua, is very complex. The complexity of the problem is caused by the existence of the fundamental distinction about the land rights between the customary society and government. As the consequence, this disagreement brings about a conflict. The cause of the land conflict in Arso is government policy in development disregarding the existence and role of the customary society as the land owner. Since the government planned to build an oil palm estate using the customary land and doing a land acquisition, the existence of the society has continued to be ignored. The land acquisition has caused a social disturbance. In addition, the government policy tends to district the customary institution by setting aside the role of the yuskwondur which is an independent institution and appointing a new yuskwondur which is just the accomplice of the government in releasing the customary land. Keywords: land conflict, Arso, policyMasalah tanah di Indonesia, termasuk Papua, sangat kompleks. Kompleksitas masalah ini disebabkan oleh keberadaan perbedaan mendasar tentang hak atas tanah antara masyarakat adat dan pemerintah. Sebagai konsekuensinya, perselisihan ini menyababkan konflik. Penyebab konflik tanah di Arso adalah kebijakan pemerintah dalam pengembangan mengabaikan keberadaan dan peran masyarakat adat sebagai pemilik lahan. Sejak pemerintah berencana untuk membangun perkebunan kelapa sawit menggunakan tanah adat dan melakukan akuisisi tanah, keberadaan masyarakat terus diabaikan. Akuisisi lahan telah menyebabkan gangguan sosial. Selain itu, kebijakan pemerintah cenderung menghilangkan peran lembaga adat dengan menyisihkan peran yuskwondur yang merupakan instution independen dan menunjuk seorang yuskwondur baru yang hanya kaki ta-ngan pemerintah dalam melepaskan tanah adat. Kata Kunci: konflik lahan, Arso, kebijakan